(untitled) (Journal of Nepal Geological Society, 2013)
The densely packed assembly of granular materials subjected to slow deformations is studied experimentally in the 2D shear flow apparatus. High speed video camera and subsequent image processing techniques help to document the positions of the particles in the flow. Effective algorithms are formulated to determine the particle rotation, group size and local particle concentrations. Experimental results depict that the consecutive cycles of solid like (jammed) and fluid like (un-jammed) states characterize the flow. The jammed state is represented by negligible mobilization of particles, whereas the un-jammed state is represented by considerable mobilization of particles. The rotational and translational kinetic energy shares their dominancy in the jammed and un-jammed states respectively. Nevertheless, rotational counterpart also increases quite high in un-jammed state. There exists clearly a gradient of translational and rotational velocity across the shear cell especially in the un-jammed state indicating the phenomenon of strain localization. The un-jammed state originates because of the breaking and buckling of few columns near to the inner moving wall as noticed by previous researchers, and the jammed state regenerates once the broken and buckled columns regrouped into new columns. The dilatation phenomenon is found to be associated with the un-jamming states indicated by the drop in the local particle concentrations.